Long-Term NMDAR Antagonism Correlates Weight Loss With Less Eating - Deng, Shi-Ning; Yan, Yu-Hua; Zhu, Tai-Lin; Ma, Bing-Ke; Fan, Hui-Ran; Liu, Yan-Mei; Li, Wei-Guang; Li, Fei (Frontiers in Psychiatry, 2019)
Memantine hydrochloride is an uncompetitive N-methyl-D-aspartate (NMDA) receptor antagonist for treatment of moderate-to-severe Alzheimer’s disease. For increased BMI and obese participants with binge eating disorder are related to a common brain area-PFC, and memantine can correct binge eating disorder, we suppose memantine might be able to treat obesity. By intraperitoneal injection and behavioral tasks, we found that long term NMDAR antagonism by memantine increased weight loss in obese mice induced by high fat diet. Memantine decreased food intake without inducing abdominal discomfort and anxiety. These results suggest that memantine might be able to be a candidate drug for obesity.